Impairment of astrocytic glutaminolysis in glutaric aciduria type I. Issue 1 (2nd November 2017) - Komatsuzaki, Shoko; Ediga, Raga Deepthi; Okun, Jürgen G.; Kölker, Stefan; Sauer, Sven W.
Abstract: Glutaric aciduria type I is a rare, autosomal recessive, inherited defect of glutaryl‐CoA dehydrogenase. Deficiency of this protein in L‐lysine degradation leads to the characteristic accumulation of nontoxic glutarylcarnitine and neurotoxic glutaric acid (GA), glutaryl‐CoA, and 3‐hydroxyglutaric acid. Untreated patients develop bilateral lesions of basal ganglia resulting in a complex movement disorder with predominant dystonia in infancy and early childhood. The current pathomechanistic concept strongly focuses on imbalanced neuronal energy metabolism due to accumulating metabolites, whereas little is known about the pathomechanistic role of astrocytes, which are thought to be in constant metabolic crosstalk with neurons. We found that glutaric acid (GA) causes astrocytic cell death under starvation cell culture conditions, i.e. low glucose, without glutamine and fetal calf serum. Glutamine completely abolished GA‐induced toxicity, suggesting involvement of glutaminolysis. Increasing dependence on glutaminolysis by chemical induction of hypoxia signaling‐potentiated GA‐induced toxicity. We further show that GA disturbs glutamine degradation by specifically inhibiting glutamate dehydrogenase. Summarizing our study shows that pathologically relevant concentrations of GA block an important step in the metabolic crosstalk between neurons and astrocytes, ultimately leading to astrocytic cell death.